2019
DOI: 10.1111/jvim.15471
|View full text |Cite
|
Sign up to set email alerts
|

Ability of ultrasonography to predict the presence and location of histologic lesions in the small intestine of cats

Abstract: Background Diagnosis of infiltrative small intestinal (SI) disease in cats is challenging, and debate continues regarding optimal biopsy techniques. Ultrasonography may facilitate selection of biopsy type and location. Hypothesis/Objectives Assess ability of ultrasonography to predict histologic lesions by SI segment and tissue layer. Animals One‐hundred sixty‐nine cats that had abdominal ultrasonography and full‐thickness SI biopsies perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
0
15
1
Order By: Relevance
“…However, our results indicated that histopathological changes and clonality results were not predictive for the development of clinical disease 10 . Moreover, studies by other groups also found poor correlation between intestinal ultrasonographic findings and health status 49 or histopathologic changes 50 . Overdiagnosis, overtreatment and false positive results have become major concerns in human medicine and led to several statements and guidelines issued by the U.S. Preventive Services Task Force, 51 National Comprehensive Cancer Network 52 and the EuroClonality/BIOMED‐2 consortium 21,22,48 .…”
Section: Discussioncontrasting
confidence: 73%
“…However, our results indicated that histopathological changes and clonality results were not predictive for the development of clinical disease 10 . Moreover, studies by other groups also found poor correlation between intestinal ultrasonographic findings and health status 49 or histopathologic changes 50 . Overdiagnosis, overtreatment and false positive results have become major concerns in human medicine and led to several statements and guidelines issued by the U.S. Preventive Services Task Force, 51 National Comprehensive Cancer Network 52 and the EuroClonality/BIOMED‐2 consortium 21,22,48 .…”
Section: Discussioncontrasting
confidence: 73%
“…In humans, dogs, and cats, ultrasound has been helpful in recognizing features of gastrointestinal disease such as the segment of bowel affected, the intestinal wall layer affected, the presence or absence of thickening, or the loss of layering pattern are indicative of specific diseases or disease processes. 9,23,[31][32][33] Although ultrasound has become a popular tool in the evaluation of horses with gastrointestinal disease, the knowledge about specific features of different diseases is sparse. This study characterizing the detailed sonographic appearance of healthy intestinal wall segments is an important first step toward clinical application in horses.…”
Section: Discussionmentioning
confidence: 99%
“…The four clinical cases were included to demonstrate that identifying intestinal layering is possible in vivo in horses. In humans, dogs, and cats, ultrasound has been helpful in recognizing features of gastrointestinal disease such as the segment of bowel affected, the intestinal wall layer affected, the presence or absence of thickening, or the loss of layering pattern are indicative of specific diseases or disease processes 9,23,31–33 . Although ultrasound has become a popular tool in the evaluation of horses with gastrointestinal disease, the knowledge about specific features of different diseases is sparse.…”
Section: Discussionmentioning
confidence: 99%
“…antigen ELISA ( n = 20), and abdominal ultrasonography. Sonographic findings were evaluated based on the presence of increased total GI wall thickness (>2.5 mm for the duodenum and jejunum and >3.2 mm for the ileum; level of increase graded as normal, mildly increased, or markedly increased [ 46 ]), loss of GI wall layering, increased thickness of the muscularis layer (>0.3 mm for the duodenum, >0.4 mm for the jejunum, and >0.9 mm for the ileum; graded as normal, mildly increased, or markedly increased [ 46 ]), enlarged mesenteric lymph nodes, and the presence of (scant) ascites [ 47 ].…”
Section: Methodsmentioning
confidence: 99%